KAPASITAS LENTUR PLAT BETON BERTULANGAN BAMBU PETUNG DENGAN TAKIKAN TIDAK SEJAJAR (ALTERNATIF PENGGANTI TULANGANBAJA PADA PLAT LANTAI RUMAH) - Dariyadi, Eko; Setiya Budi, Agus; Prayitno, Slamet (Matriks Teknik Sipil, 2014)
Bamboo is one reinforcement alternative to steel reinforcement for housing construction using reinforced concrete materials . Concrete slab itself is oneof the structural elements are made using steel reinforced concrete . This study was conducted to determine how much capacity plate reinforcedconcrete bending bamboo petung not aligned with the notch . The method used in this study is an experimental method with a concrete slabspecimen measuring 600 mm x 400 mm x 100 mm . Quality concrete is planned fc ' = 17.5 MPa . Bending test performed at 28 days with thethird point loading method . The test results of reinforced steel plate bending capacity by an average of 0.5222 ton.m and results of the analysis ofton.m 0.3051 , while the test results flexural capacity of reinforced concrete plate with a notch bamboo Petung misaligned by an average of 0.1714ton.m and the results of the analysis of 0.1097 ton - m . The test results of reinforced concrete bending stress steel plate by an average of 7.8966MPa and 6804 MPa results of the analysis of the test results while the bending stress Petung bamboo reinforced concrete plate with the notch isnot aligned average of 2.5717 MPa and 1.4204 MPa